Expatriate development for Asia-Pacific: a study of training contents and methods - Osman-Gani, Aahad M.; Tan, Wee-Liang (Inderscience Enterprises, 2005)
The emerging economies in the Asia-Pacific form a major arena of increasing overseas business operations. Yet little is known about the international HRD programmes and practices employed by companies to train and develop managers for this dynamic region. This paper presents the empirical findings of a study on the relative importance of several training content areas that are crucial for managers to succeed in overseas assignments in the Asia-Pacific region. The study is based on companies that have internationalised business opportunities in the region. In addition to identifying the profiles of international managers, the study also identified the types, contents, effective methods and duration of such training programmes.